2004
DOI: 10.1128/aac.48.11.4349-4359.2004
|View full text |Cite
|
Sign up to set email alerts
|

N-Substituted Pyrrole Derivatives as Novel Human Immunodeficiency Virus Type 1 Entry Inhibitors That Interfere with the gp41 Six-Helix Bundle Formation and Block Virus Fusion

Abstract: A recently approved peptidic human immunodeficiency virus type 1 (HIV-1) fusion inhibitor, T-20 (Fuzeon; Trimeris Inc.), has shown significant promise in clinical application for treating HIV-1-infected individuals who have failed to respond to the currently available antiretroviral drugs. However, T-20 must be injected twice daily and is too expensive. Therefore, it is essential to develop orally available small molecule HIV-1 fusion inhibitors. By screening a chemical library consisting of "drug-like" compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
278
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 251 publications
(279 citation statements)
references
References 55 publications
1
278
0
Order By: Relevance
“…In the final 6-helix bundle structure (6HB), three HR1 and three HR2 coalesce forming a highly stable antiparallel helical bundle. A number of small-molecule inhibitors of HIV-1 fusion that interfere with CD4-induced conformational changes in gp120, 8,9 coreceptor binding, [10][11][12] and the gp41 6HB formation [13][14][15][16][17][18][19][20][21][22][23][24] have been identified by high-throughput screening (HTS). Currently, only two HIV-1 fusion inhibitors (enfuvirtide and maraviroc) have been approved for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…In the final 6-helix bundle structure (6HB), three HR1 and three HR2 coalesce forming a highly stable antiparallel helical bundle. A number of small-molecule inhibitors of HIV-1 fusion that interfere with CD4-induced conformational changes in gp120, 8,9 coreceptor binding, [10][11][12] and the gp41 6HB formation [13][14][15][16][17][18][19][20][21][22][23][24] have been identified by high-throughput screening (HTS). Currently, only two HIV-1 fusion inhibitors (enfuvirtide and maraviroc) have been approved for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…This way, Jiang et al [115] identified two N-substituted pyrroles, NB-2 and NB-64 ( Fig. 13a and b, respectively), that block HIV-1 fusion and entry against both laboratory-adapted and primary HIV-1 strains at low micromolar levels.…”
Section: Hiv-1 Gp41 Inhibitorsmentioning
confidence: 99%
“…Another group, Jiang et al, also used computer-aided molecular docking analysis to show that NB-2 and NB-64 (see Fig. 13a and b) bind to the gp41 hydrophobic cavity region through hydrophobic and ionic interactions and blocks the formation of the fusion-active gp41 core [115].…”
Section: Gp41mentioning
confidence: 99%
“…As demonstrated above, the affinity of negatively charged analytes was overestimated, by a factor that appeared to correlate with analyte pI or pKa. The interaction of inhibitors in the gp41 hydrophobic pocket involves both hydrophobic and electrostatic contacts [38][39][40] , and the charge on the inhibitors plays a crucial role in binding 41,42 . It is impossible to avoid the effect of analyte charge on the ICS response 21 .…”
Section: Confirmation Of Bioreceptor Activity By Sprmentioning
confidence: 99%